Glioma Stem-Like Cells and Metabolism: Potential for Novel Therapeutic Strategies - Harland, Abigail; Liu, Xia; Ghirardello, Mattia; Galan, M. Carmen; Perks, Claire M.; Kurian, Kathreena M. (Frontiers in Oncology, 2021)
Glioma stem-like cells (GSCs) were first described as a population which may in part be resistant to traditional chemotherapeutic therapies and responsible for tumour regrowth. Knowledge of the underlying metabolic complexity governing GSC growth and function may point to potential differences between GSCs and the tumour bulk which could be harnessed clinically. There is an increasing interest in the direct/indirect targeting or reprogramming of GSC metabolism as a potential novel therapeutic approach in the adjuvant or recurrent setting to help overcome resistance which may be mediated by GSCs. In this review we will discuss stem-like models, interaction between metabolism and GSCs, and potential current and future strategies for overcoming GSC resistance.